STRUCTURAL CHANGES IN THE MUSCLE FIBER IN THE PERIOD OF ADAPTATION TO PHYSICAL ACTIVITY OF VARYING INTENSITY - Nikolai G. Belyaev (Наука. Инновации. Технологии, 2022)
In the simulation state of overtraining increases the accumulation of Ca ++ in myocytes, which is one of the causes of deterioration of cells. Licorice extract reduced the damaging effects of intense exercise on muscle cells, but it did not rule out completely.